(untitled) (Research, Society and Development, 2022)
Due to the great prominence of occupational diseases, the role of physiotherapy in work environments grows every day due to the discovery of the importance of investing in preventive actions. From this perspective, the objective was to analyze, from the scientific literature, the physical therapy interventions that are used in work-related musculoskeletal disorders. This is an integrative literature review, carried out between March and May 2022. Data collection was carried out using the following databases: LILACS, MEDLINE, PUBMED and PEDro. Primary studies available in full, analysis studies, observational studies and clinical trials, in Portuguese, English and Spanish, published between 2013 and 2022 were eligible. In turn, it was decided to exclude theses, monographs, dissertations and studies that deviated from the theme proposal. 58 studies were identified, however, after adopting the eligibility criteria, five studies were incorporated into the review. In general, the analyzed studies reported that physical therapy has a significant role in workers’ health. It is concluded that labor gymnastics and kinesiotherapy, as well as other resources, work as potential physiotherapeutic interventions in the approach of individuals with or without work-related musculoskeletal disorders, being efficient in the promotion and prevention of injuries, in the reduction of occupational stress, increased resistance to fatigue, improved posture and the performance of movements performed during work.